Severe Acute Respiratory Syndrome Coronavirus-2 Infections in Critical Care Staff: Beware the Risks Beyond the Bedside. Issue 3 (29th January 2021) - El Bouzidi, Kate; Pirani, Tasneem; Rosadas, Carolina; Ijaz, Samreen; Pearn, Matthew; Chaudhry, Shehnila; Patel, Sameer; Sureda-Vives, Macià; Fernandez, Natalia; Khan, Maryam; Cherepanov, Peter; McClure, Myra O.; et al.
Abstract : OBJECTIVES: Critical care workers were considered to be at high risk of severe acute respiratory syndrome coronavirus-2 infection from patients during the first wave of the pandemic. Staff symptoms, previous swab testing, and antibody prevalence were correlated with patient admissions to investigate this assumption. DESIGN: Cross-sectional study. SETTING: A large critical care department in a tertiary-care teaching hospital in London, United Kingdom. SUBJECTS: Staff working in critical care. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Participants completed a questionnaire and provided a serum sample for severe acute respiratory syndrome coronavirus-2 antibody testing over a 3-day period in April 2020. We compared the timing of symptoms in staff to the coronavirus disease 2019 patient admissions to critical care. We also identified factors associated with antibody detection. Of 625 staff 384 (61.4%) reported previous symptoms and 124 (19.8%) had sent a swab for testing. Severe acute respiratory syndrome coronavirus-2 infection had been confirmed in 37 of those swabbed (29.8%). Overall, 21% (131/625) had detectable severe acute respiratory syndrome coronavirus-2 antibody, of whom 9.9% (13/131) had been asymptomatic. The peak onset of symptoms among staff occurred 2 weeks before the peak in coronavirus disease 2019 patient admissions. Staff who worked in multiple departments across the hospital were more likely to be seropositive. Staff with a symptomatic household contact were also more likely to be seropositive at 31.3%, compared with 16.2% in those without ( p < 0.0001). CONCLUSIONS: Staff who developed coronavirus disease 2019 were less likely to have caught it from their patients in critical care. Other staff, other areas of the hospital, and the wider community are more likely sources of infection. These findings indicate that personal protective equipment was effective at preventing transmission from patients. However, staff also need to maintain protective measures away from the bedside.